The role of entrenchment and schematisation in the acquisition of rich verbal morphology - Hržica Gordana; Košutar Sara; Botica Tomislava Bošnjak; Milin Petar (Cognitive Linguistics)
Entrenchment and schematisation are the two most important cognitive processes in language acquisition. In this article, the role of the two processes, operationalised by token and type frequency, in the production of overgeneralised verb forms in Croatian preschool children is investigated using a parental questionnaire and computational simulation of language acquisition. The participants of the questionnaire were parents of children aged 3;0–5;11 years (n = 174). The results showed that parents of most children (93 %) reported the parallel use of both adult-like and overgeneralised verb forms, suggesting that Croatian-speaking preschool children have not yet fully acquired the verbal system. The likelihood of overgeneralised forms being reported decreases with the age of the children and verb type frequency. The results of the computational simulation show that patterns with a higher type frequency also show a greater preference for the correct form, while lexical items show both learning and unlearning tendencies during the process.